2017
DOI: 10.1371/journal.pone.0181337
|View full text |Cite
|
Sign up to set email alerts
|

Multiple approaches to understanding the taxonomic status of an enigmatic new scorpion species of the genus Tityus (Buthidae) from the biogeographic island of Paraje Tres Cerros (Argentina)

Abstract: Tityus curupi n. sp., belonging to the bolivianus complex, is described from the biogeographically distinct area of Paraje Tres Cerros in north-eastern Argentina. We also present a molecular species delimitation analysis between Tityus curupi n. sp. and its sister species Tityus uruguayensis Borelli 1901 to confirm species integrity. Furthermore, a cytogenetic analysis is presented for these two species which contain different multivalent associations in meiosis, as a consequence of chromosome rearrangements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Intraspecific variability in diploid number has been recorded in 40% of the 18 karyotyped Tityus species [ 42 , 69 ]. Similar to the species investigated herein, previous studies revealed variations at the inter- and intra-population levels and attributed differences in chromosome number to fission/fusion rearrangements [ 29 , 39 , 41 , 42 , 48 ]. In specimens of T .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Intraspecific variability in diploid number has been recorded in 40% of the 18 karyotyped Tityus species [ 42 , 69 ]. Similar to the species investigated herein, previous studies revealed variations at the inter- and intra-population levels and attributed differences in chromosome number to fission/fusion rearrangements [ 29 , 39 , 41 , 42 , 48 ]. In specimens of T .…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining specific chromosomal regions in scorpions have increased significantly in recent years [ 29 , 39 42 , 48 , 83 87 ]. Data regarding the localization of NORs and rDNA has revealed remarkable stability, particularly in Tityus species, in which more than 80% of the species presented a similar pattern, i.e., NORs/rDNA in the terminal regions of two chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations